1991
DOI: 10.1016/0021-9991(91)90001-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical approach study of spurious steady-state numerical solutions of nonlinear differential equations. I. The dynamics of time discretization and its implications for algorithm development in computational fluid dynamics

Abstract: The goal of this paper is to utilize the theory of nonlinear dynamics approach to investigate the possible sources of errors and slow convergence and nonconvergence of steady-state numerical solutions when using the time-dependent approach for nonlinear hyperbolic and parabolic partial differential equations terms. This interdisciplinary research belongs to a subset of a new field of study in numerical analysis sometimes referred to as "the dynamics of numerics and the numerics of dynamics." At the present tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…These are valid solutions of the difference equations, but they are a qualitatively different class of solution than the approximate numerical solutions to the underlying differential equations found in the limit of infinite spatial and temporal resolution. Such chaos has been observed in COYOTE [16] as well as other codes [17]- [20]. It occurs when the code is run near its stability limit.…”
Section: Another Type Of Chaos?mentioning
confidence: 81%
“…These are valid solutions of the difference equations, but they are a qualitatively different class of solution than the approximate numerical solutions to the underlying differential equations found in the limit of infinite spatial and temporal resolution. Such chaos has been observed in COYOTE [16] as well as other codes [17]- [20]. It occurs when the code is run near its stability limit.…”
Section: Another Type Of Chaos?mentioning
confidence: 81%
“…where δ 1 is the entropy fix parameter (see [36] for a discussion).Q l j+1/2 is an unbiased limiter function which can bê…”
Section: Description Of Well-balanced Methodsmentioning
confidence: 99%
“…This includes adaptive temporal and spatial schemes, grid adaptation as an integral part of the numerical solution process, and, most of all, adaptive numerical dissipation controls. Using tools from dynamical systems, Yee et al (1991Yee et al ( -1997, Yee & Sweby (1993-1997, Griffiths et al (1992a,b) and Lafon & Yee (1991 showed that adaptive temporal and adaptive spatial schemes are important in minimizing numerically induced chaos, numerically induced chaotic transients and the false prediction of flow instability by direct numerical simulation (DNS). Their studies further indicate the need in the development of practical adaptive temporal schemes based on error controls to minimize spurious numerics due to the full diseretizations.…”
Section: Adaptive Numerical Methodsmentioning
confidence: 99%
“…It was shown in Yee et al (1991) and Griffiths et al (1992a,b) that spurious discrete traveling waves can exist, depending on the method of discretizing the source term. When physical diffusion is added, it is not known what type of numerical difficulties will surface.…”
Section: Source Term Treatments In Reacting Flowsmentioning
confidence: 99%
See 1 more Smart Citation